Genetic factors influencing inhibitor development in a cohort of South African haemophilia A patients. (21st June 2014) - Lochan, A.; Macaulay, S.; Chen, W. C.; Mahlangu, J. N.; Krause, A.
Summary: A critical complication of factor VIII (FVIII) replacement therapy in Haemophilia A (HA) treatment is inhibitor development. Known genetic factors predisposing to inhibitor development include FVIII ( F8 ) gene mutations, ethnicity, a family history of inhibitors and FVIII haplotype mismatch. The aim of this study was to characterize and correlate these genetic factors in a cohort of South African HA patients. This was a retrospective study that included 229 patients and involved the analysis of patient files, HA molecular and clinical databases and molecular analysis of the F8 gene haplotype. Of the 229 patients, 51% were of black ethnicity, 49% were white, 5% had mild HA, 4% were moderate and 91% were severe, 36% were int22 positive and 13% were inhibitor positive. Of the inhibitor positive patients, 72% were black patients. Inhibitors were reported in 27% of black int22 positive patients, 13% of black int22 negative patients, 9% of white int22 positive patients and 7% of white int22 negative. The H1 haplotype was more common in whites (75%) and H2 was more common in blacks (74%). H3 and H5 were only found in black patients and had a higher frequency of inhibitor development than H1 and H2. In this small HA cohort, black patients had a significantly higher frequency of inhibitor development and the results were indicative of an association between inhibitor development, ethnicity and haplotype.